2016
DOI: 10.1242/jcs.180521
|View full text |Cite
|
Sign up to set email alerts
|

Sharing of mitotic pre-ribosomal particles between daughter cells

Abstract: Ribosome biogenesis is a fundamental multistep process initiated by the synthesis of 90S pre-ribosomal particles in the nucleoli of higher eukaryotes. Even though synthesis of ribosomes stops during mitosis while nucleoli disappear, mitotic pre-ribosomal particles persist as observed in pre-nucleolar bodies (PNBs) during telophase. To further understand the relationship between the nucleolus and the PNBs, the presence and the fate of the mitotic pre-ribosomal particles during cell division were investigated. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 38 publications
(69 reference statements)
3
29
0
Order By: Relevance
“…Indeed, inhibition of pre-rRNA transcription with ActD retarded iPNB disassembly, although pre-rRNA processing was not substantially altered. These results are in agreement with the data of Roussel and colleagues, who demonstrated that processing of pre-rRNA is not sufficient to induce disappearance of PNBs, which appears to require the presence of functional nucleoli (Sirri et al, 2016). Further studies are necessary to confirm our hypothesis.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, inhibition of pre-rRNA transcription with ActD retarded iPNB disassembly, although pre-rRNA processing was not substantially altered. These results are in agreement with the data of Roussel and colleagues, who demonstrated that processing of pre-rRNA is not sufficient to induce disappearance of PNBs, which appears to require the presence of functional nucleoli (Sirri et al, 2016). Further studies are necessary to confirm our hypothesis.…”
Section: Discussionsupporting
confidence: 93%
“…The proteins with a later recruitment could facilitate the assembly of the nucleolus during mitotic exit. Previous studies show that pre-nucleolar bodies are formed on the chromosomal periphery during telophase (Savino et al, 2001;Angelier et al, 2005;Sirri et al, 2016). Proteins showing a late chromosomal recruitment might hence be needed for the early reformation of the nucleolus after cell division.…”
Section: Discussionmentioning
confidence: 95%
“…PCRs and/or real-time qPCRs were performed using oligonucleotides corresponding to human rDNA (Sirri et al, 2016). The forward oligonucleotides were: ETS1, 5′-GAGGTTGGGCCTCCGGATGC-3′; ETS3, 5′-CCTCTGACGCGGCAGACAGC-3′; ETS5, 5′-GTCGGTGTG-GGGTTCGAGGC-3′; 5.8S1, 5′-CACTTCGAACGCACTTGCGG-3′; and 18S1, 5′-GTTCAAAGCAGGCCCGAGCC-3′.…”
Section: Primersmentioning
confidence: 99%
“…The ETS (nt +935 to +1082) and 5.8S+ (nt +6718 to +6845, numbers given relative to the transcription start site defined as the +1 position) probes corresponding to fragments of human rDNA were generated as digoxigeninlabeled using primers ETS5 and ETS6 and primers 5.8S1 and 5.8S2, respectively, and the PCR DIG probe synthesis kit (Roche, Sirri et al, 2016).…”
Section: Probesmentioning
confidence: 99%